Effects of metal nanoparticles of iron, copper and cobalt on the growth of nitrogen-fixing bacterium Sinorhizobium fredii T14 and nodulation in soybean roots - Thi Hong Thao, Phan; Thi Nhung, Dang; Thi Huong, Tran; Van Hieu, Nguyen; Thi Hong Lien, Nguyen; Mai Linh, Nguyen Vu; Hong Van, Dao Thi; Tuong Van, Nguyen; Hoai Chau, Nguyen (Vietnam Journal of Biotechnology, 2021)
Soybean is a high valuable crop of Vietnam and many other countries. The ability of soybean plants in nitrogen fixation and soil improvement is attributed to their symbiosis with different rhizobia in the root nodules. It has been well documented that members of genus Rhizobium are the most effective in nodulation and nitrogen fixation in legumes. Recently, in oder to minimize undesired accumulation of agro-chemicals and metal salts in soil, nanotechnology products have been intensively studied and applied as nanofertilizers. In this report, the effect of nanoparticles of iron, cobalt and copper on the in vitro growth of nitrogen fixing bacterium Sinorhizobium fredii T14 and nodulation in the root of soybean DT26 was studied. In the cultures of S. fredii T14, nano Fe at the final concentrations of 2, 5, 10, 25 and 50 ppm did not affect the growth, but the latter was reduced of 20, 35 and 46% at 100, 250 and 500 ppm, respectively. No growth inhibition was observed at nano Co concentrations below 10 ppm, while it was reduced of 73% at 500 ppm. Nano Cu seemed to have significant adverse effect on S. fredii T14, showing growth inhibition of 23, 68 and 100% at the concentrations of 5, 25 ppm and 50 ppm, respectively. The production of extracellular polysaccharide by S. fredii T14 was not affected at the concentrations of nano Fe and Co below 250 ppm, while drastic decrease occurred at the presence of nano Cu. Laboratory experiments showed that nanoparticles of all three studied metals at extremely low concentration of 2 ppm significantly increased the number of effective nodules in the roots of soybean DT26 and enhanced the plant growth.